Reducing the Viscosity of High Paraffin Oils by Surface Active Substances - Salihova Ozoda Abdullaevna; Nurmonov Alisher Asliddin o’g’li; Rashidov Shohzodbek Abduvahobovich (Research Parks Publishing LLC, 2021)
The aim of our work is to develop composite systems based on high and low molecular weight surfactants for cleaning various surfaces. The experimental work was carried out on a model system (quartz, glass), with an oil layer of the Dzharkurgan field deposited on its surface. In our work, to clean the water surface from oil pollution, the effectiveness of the magnetic fluid was also studied.